Subsurface Structure of Palu-Koro Fault Zone Using TOPEX Satellite Gravity Data and Regional-Residual Anomaly Separation - Rayhan Irfan Hielmy (Journal of Computation Physics and Earth Science (JoCPES), 2025)
The Palu-Koro Fault in Central Sulawesi represents a highly active tectonic feature with significant seismic hazard potential, yet detailed subsurface mapping remains challenging due to the difficult terrain in the region. This study analyzed the subsurface structure of the fault zone by utilizing TOPEX satellite gravity data to overcome accessibility issues. The primary objective was to delineate the fault geometry and characterize subsurface lithological boundaries through density contrasts. The data processing stage initially determined the average surface rock density using the Parasnis method, which yielded a precise value of 2.45 grams per cubic centimeter. This density was subsequently applied to generate the Simple Bouguer Anomaly map. To distinguish between deep-seated regional trends and shallow local structures, the study employed two filtering approaches: the second-order polynomial method and the Moving Average method. The results demonstrated that both filtering techniques yielded consistent residual anomaly patterns. The main trace of the Palu-Koro Fault was clearly identified as a continuous low-anomaly zone, interpreted as a fracture system filled with low-density sedimentary deposits. Conversely, significant high-amplitude positive anomalies were detected adjacent to the fault trace, suggesting the existence of shallow high-density bodies such as igneous intrusions or uplifted basement blocks. This research concluded that the integration of satellite gravity data with regional-residual anomaly separation successfully mapped the structural complexity of the area, providing critical baseline data for updating seismic hazard models and enhancing disaster mitigation strategies in Sulawesi.